Evaluating a novel bidirectional soft-switching DC-DC converter for electric vehicles - Inampudi, Prasannakumar; Chandrasekar, P.; Muni, T. Vijay (Institute of Advanced Engineering and Science, 2024)
This research aims to build unique zero voltage transition (ZVT) non-isolated bidirectional DC-DC converters for hybrid electric vehicle battery storage. First, a high-voltage gain bidirectional converter (BDC) is examined. This converter can soft-switch insulated gate bipolar transistors (IGBTs). The primary insulated-gate bipolar transistors (IGBTs) are operated under zero-current conditions throughout the turn-on to turn-off commutation phase to reduce switching losses and increase efficiency. A soft-switched cell with a resonant inductor, capacitor, and additional IGBTs achieves zero-current turn-off. A new converter uses insulated-gate bipolar transistors with zero-voltage transition operation. Soft-switched cells improve the hard-switched bridgeless DC-DC converter (BDC). Resonant inductors, capacitors, and auxiliary switching devices make up the soft-switched cell. Soft-switched cells enable zero voltage turn-on of primary insulated-gate bipolar transistors. This converter charges the battery in buck mode and boosts it to provide the necessary output voltage. This study examined a 70 V/300 V power system's high-gain bidirectional converter (BDC) design simulation. The converter was tested at 50 kHz with 800 W output power. The high-gain soft-switched BDC has 96.5% boost and 97% buck efficiency. Operating principles, design analysis, and simulation assessments are included in this study.